Skid Steering Tracked Vehicle Simulink Model - Ignatev, Dmitrii; Strawa, Natalia (Cranfield University, 2021)
A comprehensive mathematical model of a skid steering tracked vehicle, including track-terrain interaction, motion kinematics and dynamics, is provided. The model is also equipped with the control system for accurate following the desired trajectory. A compound identification scheme utilizing an exponential forgetting recursive least square, generalized Newton–Raphson (NR), and Unscented Kalman Filter methods is also added to estimate the model parameters, such as the vehicle mass and inertia, as well as parameters of the vehicle-terrain interaction, such as slip, resistance coefficients, cohesion, and shear deformation modulus on-line.
Keywords: unmanned tracked vehicle'; 'inertial parameters'; 'vehicle-terrain interaction'; 'identification'; 'recursive least square with exponential forgetting'; 'generalized Newton–Raphson'; 'Unscented Kalman Filter'; 'Automation and Control Engineering'; 'Autonomous Vehicles'; 'Control Systems; Robotics and Automation'; 'Mechanical Engineering'; 'Process Control and Simulation'; 'Special Vehicles'; 'Transport Engineering'